2017
DOI: 10.1038/s41598-017-04749-8
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable elastic nanofibrous platforms with integrated flexible heaters for on-demand drug delivery

Abstract: Delivery of drugs with controlled temporal profiles is essential for wound treatment and regenerative medicine applications. For example, bacterial infection is a key challenge in the treatment of chronic and deep wounds. Current treatment strategies are based on systemic administration of high doses of antibiotics, which result in side effects and drug resistance. On-demand delivery of drugs with controlled temporal profile is highly desirable. Here, we have developed thermally controllable, antibiotic-releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 44 publications
0
86
0
Order By: Relevance
“…Such capability does not exist in any existing bandages. Also, almost all the current methods and systems used for controlling drug release in the treatment of wound care are designed for topical delivery of drugs 7,15. This is due to the ease‐of‐access to the wound site, which allows for the localized delivery of therapeutics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such capability does not exist in any existing bandages. Also, almost all the current methods and systems used for controlling drug release in the treatment of wound care are designed for topical delivery of drugs 7,15. This is due to the ease‐of‐access to the wound site, which allows for the localized delivery of therapeutics.…”
Section: Resultsmentioning
confidence: 99%
“…Impaired angiogenesis significantly limits the availability of vital nutrients, oxygen, immune cells, and epithelial cells at the injury site. Without oxygen and nutrients, areas of necrotic tissue grow, which are conducive to the growth of biofilms 7. The formed biofilms on top of the wound bed are resistant to treatment by topical and systemic delivery of antibiotics 5…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies showed that the patch successfully released cefazolin in agar plates inoculated with Staphylococcus aureus and E. coli . Wound patches (1.5 cm in diameter) having heaters resulted in a zone of inhibition up to 1.0 cm over 24 h as compared to control samples without a heater …”
Section: The Rise Of Personalized Medicinementioning
confidence: 97%
“…A biodegradable electronic patch integrated with flexible heaters was developed to deliver drugs on demand . This thermally‐controllable patch allowed administering antibiotics.…”
Section: The Rise Of Personalized Medicinementioning
confidence: 99%
“…However, there also exist medical conditions which require implantable devices to work only over well‐defined periods of time. These include various applications such as monitoring, stimulating, and treating central and peripheral nervous systems after a surgery or a traumatic injury, localized drug delivery for wound healing or following a surgical procedure, as well as pressure and strain monitoring on tendons during rehabilitation after surgical repair . For such usage, transient medical devices which resorb after some time are beneficial.…”
Section: Introductionmentioning
confidence: 99%